Book Review: Chinnaiah Jangam, Dalits and the Making of Modern India, Sambaiah Gundimeda, Dalit Politics in Contemporary India and Hugo Gorringe, Panthers in Parliament Dalits, Caste and Political Power in South India. (December 2018) - Pai, Sudha
Chinnaiah Jangam, Dalits and the Making of Modern India . New Delhi: Oxford University Press. 2017. 264 pages. ₹630. Sambaiah Gundimeda, Dalit Politics in Contemporary India . New Delhi: Routledge. 2016. 294 pages. ₹1, 595. Hugo Gorringe, Panthers in Parliament Dalits, Caste and Political Power in South India . New Delhi: Oxford University Press. 2017. 424 pages. ₹995.